RANCANGAN SISTIM INFORMASI AKADEMIK DENGAN MENGGUNAKAN FRAMEWORK.NET DAN FRAMEWORK CODEIGNITER PADA SMA MARIE JOSEPH. - Simantha, Jonatan; Dasawati, Elis Sondang (Jurnal Informatika dan Bisnis, 2023)
The functions and users of technology continue to change from only highly educated people and only for large agencies to now it is used by all groups and for many purposes. Information technology is evidence of technological developments. Currently information technology has become a very common need and is used by many parties because of the many benefits it can get. The definition of a Web application framework according to Budi Raharjo, is a collection of code in the form of libraries and tools that are combined in such a way as to become a framework that facilitates and accelerates the process of developing web applications. This study uses a qualitative descriptive research method based on case studies that describe the actual situation of the subjects studied. The data collection methods used in this study were interviews and direct observation besides that, a deductive literature study served as the basis for the hypothesis. The data used in this study is data from the Marie Joseph school located in Kelapa Gading, North Jakarta,  people who usually analyze student grades and absenteeism data, one of which is data on student test scores which are stored  anually. So with this related to the application to be built, the end user or user in this case is the principal as admin and teachers, where their involvement in using this application must refer to the user specifications as follows. The Academic Information System application is able to assist teachers in making faster and more accurate reports and The Academic Information System application is capable of protecting easily damaged and lost physical data. Keywords : Framework, Codeigniter, Framework.net